148k views
5 votes
3x+4=9x-8= ????????????

User Sunilkjt
by
4.6k points

2 Answers

13 votes
Answer:

Simplifying
3x + 4 = 9x + -8

Reorder the terms:
4 + 3x = 9x + -8

Reorder the terms:
4 + 3x = -8 + 9x

Solving
4 + 3x = -8 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
4 + 3x + -9x = -8 + 9x + -9x

Combine like terms: 3x + -9x = -6x
4 + -6x = -8 + 9x + -9x

Combine like terms: 9x + -9x = 0
4 + -6x = -8 + 0
4 + -6x = -8

Add '-4' to each side of the equation.
4 + -4 + -6x = -8 + -4

Combine like terms: 4 + -4 = 0
0 + -6x = -8 + -4
-6x = -8 + -4

Combine like terms: -8 + -4 = -12
-6x = -12

Divide each side by '-6'.
x = 2

Simplifying
x = 2

God bless you “and I hope this helps”.
User BinaryNexus
by
5.3k points
11 votes
3x+4=9x-8=2 the answer would be 2
User Monstr
by
4.8k points